Heritage or Imperial Violence: A Hidden History of Early Ming Princely Acquisition of Art. (2nd July 2016) - Pang, Huiping
Abstract : The bequeathing of property within a royal family is ostensibly a clean transfer governed by clear legal codes. In the case of the Ming imperial court, many assume that imperial collections were commonly gifted from the cosmopolitan capital to the peripheral princedoms. A long-standing hypothesis holds that the first Ming emperor, Hongwu (r. 1368–98) bestowed a collection of fourth- to fourteenth-century canonical paintings and calligraphies to his sons Zhu Gang (1358–98) and Zhu Tan (1370–89) upon their enfeoffment ceremonies, but a variety of legal and cultural practices could have muddled this seemingly straightforward transaction from father to son. This paper unravels the secret of princely art acquisitions in the early Ming. It challenges existing scholarship on the transmission patterns by examining both the alleged enfeoffment gifts from Hongwu as well as multiple art confiscations during the 1390s. Zhu Gang in fact did not receive most of the artworks from his father, but seized them from several deposed officials whose power and fortune had irritated the emperor. Utilizing Hongwu's messages to Zhu Gang, which reveal the dark side of imperial gifts and property appropriations, this paper integrates the study of political and legal histories into that of the early Ming princely collecting culture.